APPLICATION OF CHATBOT AI IN THE CREATION OF WEB MINING PROGRAMS AND THEIR ANALYSIS - Ilić, Luka; Šijan, Aleksandar; Predić, Bratislav (Journal of process management and new technologies, 2023)
Artificial intelligence and ChatGPT became very popular in late November 2022. Their popularity has led to the development of other chat AI systems and AI tools. In order to monitor this progress and achieve key goals in the application of artificial intelligence, this paper has the task of presenting an analysis of the generated web mining program. One of the key aspects of this research is the presentation of advantages and disadvantages of this approach, including analysis of accuracy, speed and reliability. Also, potential challenges in the application of artificial intelligence (especially chat systems), such as the limitations of AI models, ethical and security aspects when processing data from the Internet, are explored. This research paper aims to contribute to a better understanding of the capabilities of AI in the development of web mining programs, identify potential areas of improvement and provide guidance for future development.